Anti-Inflammatory Potentials of the n-Hexane Fraction of Alstonia boonei Stem Bark in Lipopolysaccharide-Induced Inflammation in Wistar Rats - Olanlokun JO; Olowofolahan AO; Bodede O; Adegbuyi AT; Prinsloo G; Steenkamp P; Olorunsogo OO (Dove Medical Press, 2021)
John Oludele Olanlokun,1 Adeola Oluwakemi Olowofolahan,1 Olusola Bodede,2 Adekunle Theophilus Adegbuyi,3 Gerhard Prinsloo,2 Paul Steenkamp,4 Olufunso Olabode Olorunsogo1 1Laboratories for Biomembrane Research and Biotechnology, Department of Biochemistry, College of Medicine, University of Ibadan, Ibadan, Nigeria; 2Department of Agriculture and Animal Health, University of South Africa, Florida Campus, Florida, 1710, South Africa; 3Department of Pharmacology and Therapeutics, Faculty of Pharmacy, Federal University, Oye-Ekiti, Nigeria; 4Research Centre for Plant Metabolomics, Department of Biochemistry, University of Johannesburg, Johannesburg, 2006, South AfricaCorrespondence: John Oludele OlanlokunLaboratories for Biomembrane Research and Biotechnology, Department of Biochemistry, Faculty of Basic Medical Sciences, College of Medicine, University of Ibadan, Room NB 305, Ibadan, NigeriaTel +2348038014201Email jodel72000@yahoo.com; jo.olanlokun@mail.ui.edu.ngBackground: Inflammation is a protective response of the host to infections and tissue damage and medicinal plants have been used to regulate inflammatory response. The phytochemical contents of the n-hexane fraction of Alstonia boonei and their anti-inflammatory potentials in lipopolysaccharide-induced inflammation were investigated in rat liver.Materials and Methods: A quantity of 5 mg/kg lipopolysaccharide (LPS) was used to induce inflammation in twenty-five male Wistar rats, grouped (n = 5) and treated as follows: negative control (10 mL/kg saline), positive control (1 mg/kg ibuprofen); 50, 100 and 20 mg/kg of the n-hexane fraction of Alstonia boonei were administered to test groups. In another experiment, twenty rats (n = 5, without LPS) were administered the same doses of the n-hexane fraction of A. boonei and ibuprofen for seven days. At the end of the experiment, animals were sacrificed, serum was obtained from blood and liver mitochondria isolated in a refrigerated centrifuge. Mitochondrial permeability transition (mPT) pore opening and mitochondrial F0F1 ATPase (mATPase) were determined spectrophotometrically. Serum interleukins 1β, 6 (IL-1β, IL-6), tumour necrosis factor alpha (TNF-α), C-reactive protein (CRP) and creatine kinase (CK), gamma glutamyl transferase (GGT), aspartate and alanine aminotransferases (AST and ALT,) of the animals in which inflammation was induced using LPS but treated with graded doses of n-hexane fraction of A. boonei were determined using the ELISA technique. The phytochemical contents of the n-hexane fraction of A. boonei were determined using ultra performance liquid chromatography-tandem mass spectrometer (UHPLC-MS).Results: Calcium induced mPT in 8 fold and LPS induced mPT 14 fold in the negative control while the n-hexane fraction reversed mPT in the treated groups (50, 100 and 200 mg/kg) to 2, 4, 4 folds, respectively. LPS treatment of the negative group enhanced F0F1 mATPase activity, increased CRP, TNF-α, IL-1β, IL-6 levels as well as CK, AST, ALT and GGT activities. These values were significantly reduced by 100 and 200 mg/kg of the n-hexane fraction. UHPLC-MS analysis of the fraction revealed the presence of terpenoids, phenolics and sphingolipids.Conclusion: These results showed that bioactive phytochemicals present in the n-hexane fraction of A. boonei were not toxic, have an anti-inflammatory effect and could be used for the treatment of inflammatory diseases.Keywords: Alstonia boonei, endotoxins, inflammatory cytokines, liquid chromatography-mass spectrometry